2021
DOI: 10.4314/rjeste.v4i1.1
|View full text |Cite
|
Sign up to set email alerts
|

Solving an optimal control problem of hepatitis B virus dynamics: Efficacy of fuzzy logic strategy

Abstract: This work aims at using fuzzy logic strategy to solve a hepatitis B virus (HBV) optimal control problem. To test the efficacy of this numerical method, we compare numerical results with those obtained using direct method. We consider a patient under treatment during 12 months where the two drugs are taken as controls. The results are rather satisfactory. In particular, the reaction of HBV to drugs can be modeled and a feedback can be approximated by the solution of a linear quadratic problem. The drugs reduce … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Thus, the solution of optimal control problem (4), equations ( 1)-( 3) can be solved using different mathematical methods. In [18], the details about discretization, numerical solution of direct methods and approach integrating fuzzy logic are described. In this work, we focus on the perturbation iteration method.…”
Section: Problem Settingmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the solution of optimal control problem (4), equations ( 1)-( 3) can be solved using different mathematical methods. In [18], the details about discretization, numerical solution of direct methods and approach integrating fuzzy logic are described. In this work, we focus on the perturbation iteration method.…”
Section: Problem Settingmentioning
confidence: 99%
“…The starting value of the controls u 1 and u 2 is 1 if treatment is absent and is 0 in the case of maximal use of therapy. To investigate the efficacy of the perturbation iteration method, the numerical results implemented using this method are compared with one calculated by the direct method and fuzzy logic strategy [18]. Figures 1 and 2 illustrate the numerical simulation results.…”
Section: Numerical Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…And simulation of their results showed that combining these three interventions at the same time is beneficial and efficient for controlling hepatitis B infection. Other researchers such as [11][12][13][14][15] have also studied on dynamics of hepatitis B disease with optimal controls. In this work, we suggested a model for hepatitis B disease adopted from [8], including a two-dose vaccine series class, and extended it to an optimal control model to study the cost-effectiveness analysis, which was not studied by the mentioned researchers above.…”
Section: Introductionmentioning
confidence: 99%